Multi-objective Mathematical Programming Framework for Integrated Oil Sands Mine Planning and Tailings Disposal Optimization - Maremi, Ahlam; Ben-Awuah, Eugene; Askari-Nasab, Hooman (Mining engineering, 2021)
In oil sands mining, tailings are voluminous unwanted by-products generated from extracting the desired mineral from the mined ore. Dyke construction and backfilling activities require well-managed techniques to facilitate progressive reclamation at the earliest opportunity. This directly affects the sustainability and profitability of the mining operation. This research introduces a goal programming framework that simultaneously optimizes the (1) production schedule with limited duration stockpiling and directional mining; (2) dyke construction schedule; (3) size, shape, and location of tailings-cells; and (4) mining and processing production targets. The results show that in creating in-pit tailings-cells designs, decreasing the mining-cells volume and increasing the number of mining-cells improve the net present value of the operation due to increased operational flexibility. The model generated a uniform schedule for ore and practical tailings-cells designs for backfilling activities. Integrating tailings-cells optimization into oil sands mine planning and waste management ensures the efficient use of in-pit mined-out areas required for sustainable operations.